Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Magnetic materials for micro- and nanoplastics capture, separation, and detection: Material design, working mechanisms, and key challenges - Kailan Yang; Zhenqing Dai; Rijian Mo; Ruikun Sun; Shiqi Jiang; Lei He; Liming Song; Chengyong Li (Journal of Environmental Chemical Engineering, 2026)

In-situ self-assembled integrated capture-detection platform based on cuttlebone-derived organic matrix for sensitive SERS quantification of polystyrene nanoplastics - Yuping Lai; Zhenqing Dai; Kailan Yang; Rijian Mo; Ruikun Sun; Shiqi Jiang; Lei He; Jingya Zhou; Aminmuhammad Usman; Chengyong Li (Journal of Hazardous Materials, 2026)

Sea‐Level Rise Constrains the Carbon Permanence of Global Mangrove Restoration - Jincheng Wu; Zhe Zhao; Philippe Ciais; Shanshan Song; Chenyi Yuan; Guanghui Lin; Bertrand Guenet; Annemiek Stegehuis; Xiaoshan Zhu; Ruili Li; Ruikun Gou; Yuchen Meng; et al. (Global Change Biology, 2026)
Mangroves are characterized by high carbon sequestration rates, and future changes in mangrove biomass will be impacted by factors such as climate change, sea level rise, and management strategies. Here, we produce a map of present‐day global mangrove aboveground biomass (AGB) based on extensive field observations and satellite data, giving a global mangrove AGB of 1.76 Pg dry matter (DM). After accounting for potential growth to maturity, future changes in climatic and hydrological conditions, possible restoration strategies, and sea‐level rise, the global total mangrove AGB is projected to increase by 16.7% under the low‐warming scenario (Shared Socioeconomic Pathway 1 and Representative Concentration Pathway 2.6, SSP126) and decrease by 19.3% under the high‐warming scenario (SSP585) by 2100. Sea‐level rise encroaching upon the growth space of mangroves will cause a biomass loss of 41.6% in the high‐warming scenario, whereas restoration strategies would only increase AGB by 2.0%. Our study shows that sea‐level rise limits the potential of mangrove restoration to maintain carbon stocks, and regions less constrained by sea‐level rise offer greater potential for the long‐term permanence.

Succinate antagonizes α-ketoglutarate biosynthesis governing myeloid differentiation in normal hematopoiesis and myelodysplastic syndromes - Lingling Zhang; Leiming Liu; Yue Wang; Aoxue Wang; Weitao Tang; Yike Song; Zhuo Zhang; Yaqiong Chen; Dandan Liao; Huixian Liang; Fan Yang; Yiming Liu; et al. (Science Bulletin, 2026)

Microplastic pollution in the South China sea: Linking environmental abundance to fish ingestion through feeding preferences - Ruikun Sun; Jie Yang; Shiqi Jiang; Zhongxin Liang; Peilin Lei; Zhengye Xiong; Zhenqing Dai; Qingxiang Chen; Yujian Deng; Chengyong Li (Journal of Environmental Chemical Engineering, 2026)

Vertical and spatial variations of microbial communities in sediment cores from the mangrove of Gaoqiao National Nature Reserve - Jiatian Huang; Zhizhou Tan; Ruikun Sun; Zhengqing Dai; Lei He; Chengyong Li (Marine Pollution Bulletin, 2026)

Water-soluble tomato concentrate combats vascular aging through the regulation of endothelial cell senescence via DNA-sensing AIM2 inflammasome - Yujie Sun; Yufang Wang; Qingwei Zheng; Yu Wang; Mingcong Fan; Haifeng Qian; Ruikun He; Yan Li; Li Wang (Food Research International, 2026)

Pomelo peel-graphene aerogel/filter membrane with confocal Raman spectroscopy for rapid separation and identification of microplastics - Zhenqing Dai; Min Chang; Lei He; Yuping Lai; Rijian Mo; Liming Song; Ruikun Sun; Shiqi Jiang; Chengyong Li (Journal of Environmental Chemical Engineering, 2026)

Insights into the role and pathways of oxygen in NO catalytic oxidation over activated coke at sub-zero temperatures - Yue Zhang; Deao Kong; Yiding Sun; Tianyu Du; Wenhao Liu; Wenbo Li; Ruikun Wang; Yang Li; Tong Si (Journal of Environmental Chemical Engineering, 2026)

Comparative assessment of manual and UAV-based deep learning approaches for beach litter - Haiwei Li; Shiqi Jiang; Zhengye Xiong; Zhenqing Dai; Ruikun Sun; Chengyong Li (Journal of Cleaner Production, 2026)

Effects of microplastics and heavy metal stress on the growth and physiological characteristics of pioneer plant Avicennia marina - Guoli He; Huifeng Xie; Baoyi Tan; Mingqi Chen; Zijie Wu; Zhenqing Dai; Ruikun Sun; Lei He; Chengyong Li (Marine Pollution Bulletin, 2025)

Unraveling individual and combined toxicity of microplastics and tetracycline at environment-related concentrations to coral holobionts - Shiqi Jiang; Lei He; Linglong Cao; Ruikun Sun; Zhenqing Dai; Yan-Qiu Liang; Lei Ren; Shengli Sun; Chengyong Li (Journal of Hazardous Materials, 2025)

Ocean current modulation of the spatial distribution of microplastics in the surface sediments of the Beibu Gulf, China - Liyuan Wu; Chengyong Li; Chao Huang; Yongyi Luo; Jiang Huang; Fajin Chen; Xin Huang; Ruikun Sun (Journal of Hazardous Materials, 2025)

Toxicity of microplastics and nano-plastics to coral-symbiotic alga (Dinophyceae Symbiodinium): Evidence from alga physiology, ultrastructure, OJIP kinetics and multi-omics - Shiqi Jiang; Huiting Lu; Yingyin Xie; Tingrui Zhou; Zhenqing Dai; Ruikun Sun; Lei He; Chengyong Li (Water Research, 2025)

European bilberry extract reduces high-temperature baked food-induced accumulation of Nε-carboxymethyllysine and Nε-carboxyethyllysine in vivo - Xiaoxing Mo; Lihui Shen; Xinyu Wang; Yunhong Sun; Ruijie Cheng; Wenwen Chen; Juan Chen; Ruikun He; Liegang Liu (Food Research International, 2024)

Effects of microplastics on typical macrobenthos in sargassum ecosystems - Jiong Wu; Shiqi Jiang; Jiaxin Zhang; Ruikun Sun; Wen Lu; Xing Chen; Zhenqing Dai; Zhonglian Lian; Chengyong Li (Environmental Research, 2024)

Fiddler crabs (Tubuca arcuata) as bioindicators of microplastic pollution in mangrove sediments - Xiaohan Xu; Lei He; Fei Huang; Shiqi Jiang; Zhenqing Dai; Ruikun Sun; Chengyong Li (Chemosphere, 2024)

Rapid analysis of Bacillus cereus spore biomarkers based on porous channel cuttlebone SERS substrate - Yuping Lai; Guangzheng Jiang; Tianhang Liang; Xiaoxin Huang; Wanjun Jiang; Wenhui Xu; Ruikun Sun; Zhenqing Dai; Chengyong Li (Analytica Chimica Acta, 2024)

High sensitivity in quantitative analysis of mixed-size polystyrene micro/nanoplastics in one step - Wenhui Xu; Zhenqing Dai; Xiaoxin Huang; Guangzheng Jiang; Min Chang; Chenying Wang; Tingting Lai; Huanming Liu; Ruikun Sun; Chengyong Li (Science of The Total Environment, 2024)

Pyrolysis reaction mechanisms and chlorine migration of tetrachlorobiphenyl a through the integration of ReaxFF-MD and DFT - Cen Sun; Aixue Zhu; Ruikun Wang; Huixin Liu (Journal of Environmental Chemical Engineering, 2024)

Microplastics modify the microbial-mediated carbon metabolism in mangroves - Huifeng Xie; Bingbing Li; Zifan Lu; Zitang Liao; Dan Li; Lei He; Zhenqing Dai; Ruikun Sun; Shengli Sun; Chengyong Li (Environmental Chemistry Letters, 2024)

Differences in toxicity induced by the various polymer types of nanoplastics on HepG2 cells - Lihua Ma; Zijie Wu; Zifan Lu; Linhong Yan; Xiaoling Dong; Zhenqing Dai; Ruikun Sun; Pengzhi Hong; Chunxia Zhou; Chengyong Li (Science of The Total Environment, 2024)

Distribution and risk assessment of microplastics in typical ecosystems in the South China Sea - Xuanjing Zheng; Ruikun Sun; Zhenqing Dai; Lei He; Chengyong Li (Science of The Total Environment, 2023)

Plastic wastes and surface antibiotic resistance genes pollution in mangrove environments - Ruikun Sun; Yu Liu; Ting Li; Zhong-Ji Qian; Chunxia Zhou; Pengzhi Hong; Shengli Sun; Chengyong Li (Environmental Monitoring and Assessment, 2023)

Occurrence of antibiotic resistance genes carried by plastic waste from mangrove wetlands of the South China Sea - Ruikun Sun; Ting Li; Shijie Qiu; Yu Liu; Zijie Wu; Zhenqing Dai; Yuantao Liao; Xin Chen; Shuying Chen; Chengyong Li (Science of The Total Environment, 2023)